Physical problems of patients in terminal stage of cancerous disease in comparison with the social support from nursing staff - Glińska, Jolanta; Adamska, Ewa; Brosowska, Beata; Lewandowska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Terminal period of cancerous disease causes many negative results in various aspects of the life. People with cancers feel many physical symptoms except psychologist problems. Majority of them don’t manage with that and they have demanded the support from other people. The therapeutic team has the big role in this case, especially the nurse. She has the nearest and long-lasting contact with a patient, with his (her) family and with all members of the therapeutic team. Aim. The estimation of physical stage of patients in terminal period of cancerous disease and their expectations in the face of nursing staff. Material and methods. The estimation of physical stage of patients in terminal period of cancerous disease and the social support from nursing staff. Statistical analysis was performed using non-parametric test: Pearson chi 2 squared test. Results. The research has showed that the patients feel many somatic problems. The first one is stuffiness, tiredness, weariness and the next: nausea, vomiting, constipation. The itching and dryness of the skin is the most nagging problem from the skin. To make an analysis the kinds of the support in connection of availability you can see that the results have comparable value. The influence of the social support has been showed.